Traumatic Periprosthetic Acetabular Fracture Treated with One-Stage Exchange and Bone Reconstruction Using a Synthetic Bone Graft Substitute - Jan Svacina (Case Reports in Orthopedics)
A case of a traumatic periprosthetic acetabular fracture in an elderly patient, which was treated by one-stage hip exchange with implantation of an antiprotrusio cage and reconstruction of the acetabular bone loss with an injectable calcium sulphate/hydroxyapatite bone graft substitute, is reported. The paste-like bone graft substitute was injected through the holes of the antiprotrusio cage. After a setting time of 15 minutes, a low-profile cup was cemented onto the cage using polymethylmethacrylate and a new stem was inserted. The patient was encouraged to ambulate three days postoperatively weight-bearing as tolerated. At the one-year follow-up visit the patient was ambulatory and full weight-bearing without any walking aids. The follow-up radiographs demonstrated stable position and articulation of the revision hip arthroplasty with no signs of loosening of the antiprotrusio cage. However, the most interesting finding was that the bone graft substitute had remodelled to a great extent into bone. This calcium sulphate/hydroxyapatite composite shows high osteoconductive potential and can be used to regenerate bone stock in revision arthroplasty.